2019
DOI: 10.1016/j.ijid.2018.11.367
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche modeling as a tool for prediction of the potential geographic distribution of Bacillus anthracis spores in Tanzania

Abstract: Introduction: Anthrax is caused by the spore-forming, Gram-positive bacterium Bacillus anthracis. The aim of this study was to predict the potential distribution of B. anthracis in Tanzania and produce epidemiological evidence for the management of anthrax outbreaks in the country. Methods: The Maxent algorithm was used to predict areas at risk of anthrax outbreaks based on the occurrence and environmental data in Arusha and Kilimanjaro regions; the model was later transferred to predict the entire country. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
(50 reference statements)
3
28
0
Order By: Relevance
“…It has advantages over other species distribution modelling as it requires species presenceonly data, and both categorical and continuous variables can be used (Dudik et al 2004;Phillips and Dudík 2008). Several studies have demonstrated MaxEnt's ability to accurately predict species distribution in a wide range of ecological and geographical regions (Thuiller et al 2005;Yi et al 2018;Mwakapeje et al 2019). Subsequently, conservation practitioners have been increasingly using habitat suitability models from MaxEnt to make management decisions (Loiselle et al 2003;Saatchi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has advantages over other species distribution modelling as it requires species presenceonly data, and both categorical and continuous variables can be used (Dudik et al 2004;Phillips and Dudík 2008). Several studies have demonstrated MaxEnt's ability to accurately predict species distribution in a wide range of ecological and geographical regions (Thuiller et al 2005;Yi et al 2018;Mwakapeje et al 2019). Subsequently, conservation practitioners have been increasingly using habitat suitability models from MaxEnt to make management decisions (Loiselle et al 2003;Saatchi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The method is widely used for: (i) modelling the potential range of distribution of a species; and, (ii) modelling the potential area of distribution of the disease based on the assumption of its coincidence with the pathogen's geographical range. Examples of the latter approach are studies by Peterson et al and Rose and Wall on viral diseases [53,54]; Du et al on myasis [55]; Abdrakhmanov et al [56,57]; Mwakapej et al [58] on anthrax. A conceptual review of the application of the MaxEnt method in biogeography is given in [59].…”
Section: Geospatial Analysismentioning
confidence: 99%
“…All three types of anthrax are implicitly fatal in wildlife, livestock, and human beings, if not treated promptly (7). Due to B. anthracis' virulence, tenacious anthrax cases and repetitive outbreaks, concerns have been raised across continents in recent years, e.g., sub-Saharan Africa (8), Asia (9), Europe (10), Australia (11), and the United States of America (12). Also due to its potential use for bioterrorism, anthrax is considered as a global public health threat (13).…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of avian and mammalian scavengers (18), rending the carcass apart, frees a multitude of B. anthracis bacteria. Subsequently, scavengers may disperse the bacteria over a wide range through ingestion and bathing resulting in contamination of water bodies (8). Human beings, livestock, and wildlife will invariably encounter each other or share habitats which would cause a spill back or spillover of the infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation